Effects of Mg content on microstructure and electrochemical properties of Zn–Al–Mg alloys - Yao, C.; Tay, S.L.; Zhu, T.; Shang, H.; Gao, W. (Elsevier, 2015)
Zn-Al-Mg cast alloys with different Mg contents were prepared and characterized in this research. The solidification process of melt liquids and the formation mechanism of intermetallic were analyzed. The influence of microstructure on corrosion resistance property of alloy was also investigated. Results show that the microhardness of Zn-Al-Mg alloys increase with the increasing of Mg content, which is due to the grain refining effect. Ternary eutectic structures (Zn/Al/Zn-Mg intermetallic) were found in Zn-Al-Mg alloys. Polarization analyse reveals that Zn-5 wt.% Al-2 wt.% Mg (ZA5M2) alloy has the lowest corrosion current density of 1.03 × 10-3 A/cm2 among all tested samples. Electrochemical impedance spectroscopy indicates that with the increasing of Mg content, the resistance of corrosion product increases from about 930 Ω of Zn-5 wt.% Al alloy to 8360 Ω of ZA5M2 alloy. The formation of nanostructured eutectic Zn/Al/Mg2Zn11 is probably the key factor of the improved corrosion property.